STUDENTS’ ABILITY IN WRITING APPLICATION LETTER - Siti Safura; Cut Mawar Helmanda; Nengsi Aria Riski (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2020)
The aims of this study are to find out the students’ ability in writing application letter in general. This study done at english department Muhammadiyah Aceh University, while the students of semester four were taken as the participants. This study is a descriptive quantitative in which the students’ worksheets and interview are used as the instruments. The result of data analysis shows that the students’ ability in writing application letter is very good. The highest aspect of writing which mastered by the students is mechanic, while the lowest aspect of writing is grammar. Then, the data shows that the grammar mastery affect the students’ ability in writing paragraph process in which the students do not able to express their written ideas if they do not know how to write grammatically correct in english. The significance of this study is pointed to the lecturers and the students. For the lecturers, it is expected that they can evaluate the students’ ability in writing application letter, especially to support their ability in english, and for the students, it is expected that they can get better ways in improving their ability in writing application letter.